Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content: 1. The reality of organizational isolation in the public sector in Saudi Arabia Mrs. Hussah Mohammed Alareifi, Dr. Najla Ibrahim Alshenaifi 2. The effect of global energy price fluctuations on oil derivative prices and domestic prices in Jordan: GARCH model Mrs. Saba Bassam Al-Damour, Co-Prof. Radi Mohammad Adailah, Co-Prof. Ahmad Abedalqader Al-Majali 3. The mediating role of service adequacy in the relationship between follow-up and evaluation and service quality "Case study on commercial banks – Sudan – Elobied" Co-Prof. Mostafa Adam Mohammed, Asst-Prof. Adam Yagoub Abker, Co-Prof. Abdelaziz Hassan Abdelaziz 4. The reality of Sustainable Leadership practice: An exploratory study on King Saud University During the period January to February of 2023 Mrs. Majd Talal Alamri, Prof. Khalid Mohammed Alaiban 5. Online Arbitration for the Settlement of Disputes in the Contracts of Electronic Commerce Mrs. Renad Abdulkarim Alseadoon, Mr. Abdulkarim Mohammad Alseadoon , Dr. Mohammad Abdastar Abdulwhab 6. The effect of work environment conditions on the performance of workers in Lebanese private hospitals during the Lebanese financial crisis: The case of private hospitals in North Lebanon Mr. Ghassan Fawaz Fathallah, Co-Prof. Khaled Kamal-El-Din 7. The added value of internal auditing in reducing creative accounting practices Dr. Mozamil Awad Taha